Association of Smoking on Sputum Conversion Rate in Patient with Drug Sensitive Pulmonary Tuberculosis - Hussain, Zakir; Iqbal, Zafar; Safi, Abdullah; Shah, Muhammad Khalid; Fawad Ullah; Waseem Ul Haq (Indus Journal of Bioscience Research, 2025)
Background: Pulmonary tuberculosis is a common infectious disease and still a major public health problem in developing countries. Smoking is an important risk factor which impair lung defence and immune response, leading to poor treatment outcomes and delayed recovery in patients. Objective: To determine the association of smoking on sputum conversion rate in patients with drug sensitive pulmonary tuberculosis. Study Design: Prospective cohort study. Duration and Place of Study: This study was conducted from 26th March 2025 to 26th June 2025 at Department of Pulmonology, Lady Reading Hospital, Peshawar. Methodology: A total of 144 patients aged 18–60 years were included, with 72 smokers and 72 non-smokers. Diagnosis was made on chest X-ray and microbiological confirmation, and all patients received standard anti-tuberculous therapy. Sputum conversion was assessed after two months of treatment. Data were analysed using SPSS version 26. Chi-square test and Fisher exact test were applied. Results: Mean age of smokers was 39.86 ± 12.82 years and non-smokers were 40.46 ± 11.94 years. Sputum conversion was observed in 51 (70.8%) smokers and 60 (83.3%) non-smokers with relative risk 0.85 (95% CI: 0.71–1.02) and p = 0.074. Among males, conversion was significantly lower in smokers 51 (70.8%) compared to non-smokers 34 (97.1%) (p = 0.002). Conclusion: Smoking show negative effect on sputum conversion and delay treatment response in pulmonary tuberculosis, although overall association was not statistically significant.